MANAJERIAL KEPALA SEKOLAH PADA OLIMPIADE MADRASAH INDONESIA (OMI) - Ummi, Laila Nur; Suriansyah, Ahmad; Harsono, Arta Mulya Budi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Effective leadership is very significant in developing the quality of education in schools, especially through the implementation of competitive academic programs. The Indonesian Madrasah Olympiad (OMI) program acts as a major initiative to facilitate student academic excellence in this context. The purpose of this study is to explore the importance of the principal's role in managing the OMI program in the madrasah environment, focusing on managerial, instructional, and transformational aspects of leadership. The method used in this study is a case study using a qualitative approach, as well as information gathering through interviews, direct observation, and documentation at a designated madrasah. The results of the study show that the principal actively motivates students and teachers, provides the necessary resources and financial support, and introduces innovative practices to improve academic quality. The OMI program has a positive impact on student motivation, teacher competence, and parent and community participation. A structured evaluation and follow-up system is implemented to ensure the continuity and improvement of the program's results. These findings confirm that efficient leadership from the principal is crucial in optimizing the implementation of academic competencies, which greatly contributes to improving the quality of education in madrasahs.